US AND IRAQI KURDS’ RELATIONS BETWEEN 1945 AND 2011: AN INTEREST-BASED POLICY - 1945 VE 2011 YILLARI ARASINDA ABD VE IRAKLI KÜRTLERIN ILIŞKILERI: ÇIKAR EKSENLI BIR POLITIKA - Sefa Mertek (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Although the US and Iraq relations have vital importance for the Middle East, little is known about relations between the US and Iraqi Kurds. Iraqi Kurds live in the Northern area of Iraq and throughout history, they have had an impact on both Iraq and the region. This article focuses on the US and Iraqi Kurds’ relations from the beginning to Arab Spring with the perspective of realism. Relations between the US and Iraqi Kurds were examined within three time periods, characterized by touchstone events in history, namely the Second World War, the Gulf War and the Iraq War. The relations between the US and Iraqi Kurds contribute considerably to our understanding of the balance of politics at the micro level in Iraq and the macro level in the region. This study investigates whether Iraqi Kurds can be gainful or the US. As a result, because of the US’ interest-based realism, the US is always gainful.